We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

Show an equation of the tangent to the curve 𝑦 = 𝑥^5 − 3𝑥^2 +𝑥 + 5 at the point (−1, 0) is given by 𝑦 = 12(𝑥 +1) by differentiation

Guest Dec 1, 2018

edited by
Guest
Dec 1, 2018

#1**+1 **

Show an equation of the tangent to the curve 𝑦 = 𝑥^5 − 3𝑥^2 +𝑥 + 5 at the point (−1, 0) is given by 𝑦 = 12(𝑥 +1) by differentiation

y' = 5x^4 - 6x + 1

The slope of the tangent line at (-1,0) is

y' (-1) = 5(-1)^4 - 6(-1) + 1 = 12

The equation of the tangent line to (-1,0) is

y = 12 ( x - 1) + 0

y = 12(x - 1)

CPhill Dec 1, 2018